Ранний этап катакомбной культуры в Крыму: хронологический аспект - Копьева, Т.А. (Археологический альманах, 2009)
The article is devoted to the problem of the Early Catacomb monuments of the Crimea. Nowadays, there are more than 500 burial assemblages of the Catacomb Culture on the Crimean steppe and foothills. The early Catacomb monuments are represented by the burial in the barrows.